Experimental fiction or classical story-telling?: Alexander Kluge’s multi-media authorship - Uecker, Matthias (University of Wisconsin Press, 2017)
Alexander Kluge has created a huge oeuvre concerned with history and story-telling. His books, combine short narrative forms into large constructions in which the different parts all complement each other and create a seemingly never-ending series of connections which endeavour to create a portayal of the world – past, present, and future – both as it is and as humans imagine and wish it to be. Kluge’s story-telling challenges the established distinctions between genres and media as well as the distinction between fact and fiction. It also challenges established modes of publication and reception. While the organisation of Kluge’s book can be described as experimental, they make use of long-established forms of story-telling. The paper will investigate the relationship between classical forms and experimental challenges in Kluge’s work.